The effectiveness of inactive arcanobacterium pyogenes vaccines in mice - Hasan Hüseyin Hadimli*; Zafer Sayın; Yasemin Pınarkara; Aslı Sakmanoğlu; M. Seyyide Temimhan; Osman Erganiş (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine effectiveness of inactivated Arcanobacterium pyogenes vaccines adjuvanted with mineral oil (MO) and aluminum hydroxide + ginseng [Al(OH3) + G] in mice. Materials and Methods: Inactive A. pyogenes vaccines were subcutaneously administered to mice twice at 3 weeks intervals. Mice were subcutaneously challenged with live A. pyogenes according to LD50 at 15th day after second vaccination. Mice were observed for mortality and morbidity during 20 days. Death animals were necropsied and microbiological examination were made from internal organs (liver, spleen, lungs, heart and kidney). Blood samples were collected before vaccination and at 15th day after vaccination. The titers of antibodies against A. pyogenes in serum samples were detected by using self-made modified Enzyme Linked Immunosorbent Assay (ELISA). Results: Levels of antibodies in sera of vaccinated animals were significantly higher than the controls. While no mortality and morbidity were observed in vaccinated and challenged mice, both morbidity and mortality were determined in non-vaccinated mice. Conclusion: Inactive A. pyogenes vaccines prepared from local A. pyogenes strain was found to be useful to protect mice from the infection of A. pyogenes.